The Effectiveness of Liquid Trichoderma harzianum Application in Enhancing Tomato Growth (Solanum lycopersicum L.) and Suppressing Fusarium Wilt Disease - Riana, Nanda; Harman Hamidson; Chandra Irsan (Universitas PGRI Palembang, 2025)
Trichoderma is used as a biological control agent, this fungus has microparasitic and antibiotic properties against soil-borne pathogens. This study aims to investigate the impact of Trichoderma on tomato growth and the progression of Fusarium wilt disease infection. The method used was the Complete Randomized Design (CRD) method. Data from the observation of the intensity of Fusarium wilt disease attack on tomato plants with treatments (P1, P2, P3, P4, P5) showed no significant differences. The treatment of Trichoderma on plant height, number of leaves, number of flowers, number of fruits, and intensity of attack did not have a significant effect in suppressing the development of Fusarium wilt disease infection in tomato plants. Trichoderma application treatment that had the highest effect on tomato plant growth was found in treatment P4 (tomato seedlings soaked for 25 minutes using Trichoderma). The treatment with the lowest intensity of Fusarium wilt attack was found in treatment P5 (Trichoderma incubation in the soil 10 days before planting), showing a better reduction in wilt intensity compared to other treatments.